Efektifitas Rekrutmen Badan Adhoc Penyelenggara Pemilu 2024 pada Komisi Pemilihan Umum Kabupaten Sinjai - Nursaifullah, Nursaifullah; Fitriani, A; Agussariman, Agussariman; Supianti, Helda (Journal of Government Insight, 2024)
This research aims to determine the effectiveness of the recruitment of the 2024 Election Organizing Adhoc Agency, especially in the recruitment of PPK and PPS at the Sinjai Regency KPU, as well as to identify the obstacles and impacts that arise after the recruitment is carried out. This research uses qualitative descriptive-analytical methods. The results show that the implementation of recruitment for the 2024 Election Organizing Adhoc Body at the Sinjai Regency KPU has proceeded according to the stages regulated by the Indonesian KPU. Socialization has been done through social media such as Facebook (KPU Sinjai) and Instagram (@kpu_sinjai). However, overall, the implementation of recruitment has not been effective because the preparation of files and registration via the SIAKBA application (Information System for KPU Adhoc Agency Members) as well as the online CAT test are still having network problems, thus detrimental to prospective applicants. Apart from that, the results of the interview test are still influenced by the interests of insiders close to the selection team. Obstacles in recruiting an Ad Hoc Election Organizing Body at the Sinjai Regency KPU include the problem of an unstable internet network and the readiness of human resources for prospective organizers, not all of whom can understand the SIAKBA application and CAT test.